1997
DOI: 10.1016/s0006-2952(97)00039-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarizing Factors

Abstract: There is now overwhelming evidence for factors, other than nitric oxide (NO), that mediate endothelium-dependent vasodilation by hyperpolarizing the underlying smooth muscle via activation of Ca2+-activated K+ channels. Although the identity of endothelium-derived hyperpolarizing factor (EDHF) remains to be established, cytochrome P450 (CYP)-dependent metabolites of arachidonic acid (AA), namely, the epoxides, fulfill several of the criteria required for consideration as putative mediators of endothelium-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 100 publications
3
94
1
1
Order By: Relevance
“…Studies, largely performed in animals, found that such stimuli are associated with remodelling and antiatherogenic effects (e.g. eNOS-expression/activity (Awolesi et al 1995), EDHF-synthase expression (Quilley et al 1997)). Alternative systemic mechanisms may relate to novel markers, such as endothelial progenitor cells (EPCs) and miRNA .…”
Section: Discussionmentioning
confidence: 99%
“…Studies, largely performed in animals, found that such stimuli are associated with remodelling and antiatherogenic effects (e.g. eNOS-expression/activity (Awolesi et al 1995), EDHF-synthase expression (Quilley et al 1997)). Alternative systemic mechanisms may relate to novel markers, such as endothelial progenitor cells (EPCs) and miRNA .…”
Section: Discussionmentioning
confidence: 99%
“…EDHF causes endothelium-dependent NOS/COX inhibitor-insensitive hyperpolarization and relaxation of vascular smooth muscle that is blocked by inhibitors of calcium-activated potassium channels such as charbydotoxin and apamin but not by inhibitors of ATP-sensitive potassium channels. 34 Although the identity of EDHF may vary among vascular beds and species, mounting evidence suggests that EDHF is a cytochrome P 450 epoxygenase-derived product of arachidonic acid. 35 The contribution of EDHF to BKstimulated vasodilation in human arteries in vitro has been demonstrated, 30,36 and recent work by Taddei et al 37 indicates that prevention of hyperpolarization by ouabain attenuates the forearm vasodilator response to BK in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current opinion is that the synthesis of EDHF is secondary to the activation of phospholipase A 2 (PLA 2 ), and the liberation of arachidonic acid (Quilley et al, 1997). Indeed, the synthesis of EDHF is thought to be Ca 2+ -dependent by virtue of the reported Ca 2+ -dependency of PLA 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the synthesis of EDHF is thought to be Ca 2+ -dependent by virtue of the reported Ca 2+ -dependency of PLA 2 . Thereafter, the signalling pathway is obscure and although EDHF may be generated from arachidonic acid by CYP enzymes in some vascular beds this is almost certainly not the case in others (Mombouli & Vanhoutte, 1997;Quilley et al, 1997). Since the EDHF produced in all of the arteries under investigation has been pharmacologically characterized as a CYP-dependent metabolite of arachidonic acid, it seemed plausible to suggest that the CB1 agonists attenuated EDHF production by decreasing the activity of the`EDHF synthase'.…”
Section: Discussionmentioning
confidence: 99%